Analysis of Pedestrian Facility Planning (Case Study of Peta Street in Bandung City) - Stefanus Sylvan Ryanto; Hazen Putraditya Mochammad; A. A. Bagus Oka Khrisna Surya (PT. Alpha Trianguli Australis, 2025)
The Peta Road corridor in Bandung City lacks adequate pedestrian facilities, particularly in front of SPBU 34-40256, despite the high intensity of pedestrian activities generated by nearby schools, industrial areas, and residential zones. This condition increases the risk of vehicle–pedestrian conflicts and is reflected in recurrent pedestrian-related accidents recorded during the 2019–2023 period. This study aims to plan appropriate pedestrian walking and crossing facilities based on actual demand to enhance pedestrian safety and comfort. The required sidewalk width was calculated using technical guidelines issued by the Ministry of Public Works and Housing, resulting in a theoretical width of approximately 1.1 m; however, an operational width of 1.5 m on both sides of the road is recommended to meet safety and accessibility standards. The peak pedestrian flow along the road segment reached 2.45 pedestrians/min on one side and 2.75 pedestrians/min on the opposite side. For crossing facilities, the peak crossing volume (P) was 191 pedestrians/hour and the peak traffic volume (V) was 6,103 vehicles/hour, producing a PV² value of 7.1 × 10⁹. Based on this value and site constraints, a pelican crossing is recommended as the most appropriate and technically justified pedestrian crossing facility for the study location.